Digitalization of Online Single Submission as a Manifestation of Integrated Services at DPMPTSP Kepulauan Riau Province - Nosy Syarfita; Rudi Subiyakto; Edi Akyari (Kemudi, 2024)
This research target is in line with the basic problems that will be revealed related to the positive significance of the digital transformation policy implementation process at the Kepulauan Riau Province Investment and One-Stop Integrated Service Office and the dominant obstacles faced related to the digital transformation policy implementation process at the DPMPTSP of Riau Islands Province. The relationship between these problems will be explored using a qualitative approach as a tiered research design supported by the availability of Grindle's approach to policy implementation and the linear relevance of the locus under study. The parameters of the findings by Mergel, et al. (2019), in order to meet public expectations of the Government's ability to provide high-value real-time digital services, the Government changed operational standards to improve public services to be more effective so as to achieve goals, including transparency and public satisfaction. The indicators of these research findings indicate the existence of relevance and linear comparison as novelty which is the author's target in providing research novelty. The achievement of research targets is supported by qualitative methods and descriptive analysis and discussion of field observations segmented within the scope of field research. However, after the author completed an initial survey at the Kepri Province Investment and One- Stop Integrated Service Office, indicating the relevance of the research findings that the added value of the community is obtained as needed, namely fast, easy, and free of charge, the function of NIB which also applies as a business license, distribution permit, SNI, and Halal Certificate, through OSS-RBA, MSE and Non MSE business actors. A number of conclusions followed by positive and negative implications indicate a multiplying effect on research findings directly and indirectly which can be used as empirical evidence for policy making related to online licensing in Riau Islands Province.